Misalignment of plastic and evolutionary responses of lifespan to novel carbohydrate diets - Vikram P. Narayan; Nidarshani Wasana; Alastair J. Wilson; Stephen F. Chenoweth (Royal Society Open Science, 2024)
Diet elicits varied effects on longevity across a wide range of animal species where dietary discordance between an organisms' evolutionary and developmental dietary history is increasingly recognized to play a critical role in shaping lifespan. However, whether such changes, predominantly assessed in a single generation, lead to evolutionary shifts in lifespan remains unclear. In this study, we used an experimental evolution approach to test whether changes in an organisms' evolutionary and developmental dietary history, specifically carbohydrate content, causes lifespan evolution in Drosophila serrata. After 30 generations, we investigated the evolutionary potential of lifespan in response to four novel diets that varied systematically in their ratio of carbohydrate–protein content. We also examined developmental plasticity effects using a set of control populations that were raised on the four novel environments allowing us to assess the extent to which plastic responses of lifespan mirrored adaptive responses observed following experimental evolution. Both high- and low-carbohydrate diets elicited plastic effects on lifespan; however, the plastic responses for lifespan to developmental diets bore little resemblance to the evolved responses on evolutionary diets. Understanding the dietary conditions regulating the match/mismatch of plastic and evolved responses will be important in determining whether a particular match/mismatch combination is adaptive for lifespan. While the differences in evolutionary diet by developmental diet interactions are only beginning to be elucidated, this study lays the foundation for future investigations of carbohydrate contributions to evolved and plastic effects on health and lifespan.